LIVRO DIDÁTICO DE LÍNGUA INGLESA E SUAS TAREFAS DE LEITURA - Azevedo, Luciane Monteiro (2015)
Reading tasks are of great importance to the students` learning process for they help in the acquisition of knowledge, in the reflection about different textual relations and for the student`s active participation in the construction of meaning. This research aims at investigating the reading tasks presented in English textbooks and is justified by the fact that these textbooks have been adopted for the last four years in Public Schools in the Paraná State. The research begins with the revision of concepts related to the reading area, the analysis of how the act of reading occurs, as well and the skills and competences required to it. This is an important instrument in the social and educational life of the subject, for it goes beyond decoding and involves many processes of interaction with the text. Following, the history of the textbook in Brazil is presented since this material is constituted as an important part in the reader formation and also because a great part of the teachers use it as a printed source of information. As the principal part of this study there is the presentation of the analysis of the reading tasks brought by the textbooks "Prime: Inglês para o Ensino Médio", for high school and "Vontade de Saber Inglês" for junior high school students, both used in the Public Schools in Guarapuava, Paraná. The analysis of the textbooks was conducted based on the taxonomy of Reading Literacy Subscales used by the Programme for International Student Assessment (PISA), which is divided into 3 domains (Reading for Information, Interpreting Texts and Reflecting and Evaluating) and 5 levels, being 1 the most basic and 5 the highest in the Subscale regarding reading skills and abilities. 196 reading tasks were selected and analyzed in this study, comprising 28 tasks for each textbook from each series under consideration. Data analysis reveals that although the reading tasks include the 3 domains of the Subscale in all the school years, they do not include all the reading levels (1, 2, 3, 4 and 5). That is to say, there are no occurrences of reading tasks in levels 4 and 5 that require skills and abilities of higher order, as for instance, generation of inferences, construction of main idea of implicit information, or when there is concurrent information. Level 3 reading tasks are practically nonexistent in high school with 3,57% in the reading for information domain, 3,57% and 10,71% in the reflecting and evaluating domain. These percentages do not reflect the minimum so as the high school graduate can be able to perform satisfactorily the tasks required by the society that surrounds him and envisions an active and critic citizen.